Sarah Orne Jewett - Thorp, Margaret Farrand, 1891-1970 (University of Minnesota pamphlets on American writers ;, 1966)
Sarah Orne Jewett - American Writers 61 was first published in 1966. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.